Burden of Disease in Real-Life Setting of Patients With Atopic Dermatitis: Italian Data From the MEASURE-AD Study - Giuseppe Argenziano; Santo Raffaele Mercuri; Paola Savoia; Paolo Amerio; Anna Belloni Fortina; Maria Rita Bongiorno; Maria Beatrice De Felici Del Giudice; Aurora Parodi; Nicola Pimpinelli; Luca Stingeni; Michela Ortoncelli; Giuseppe Stinco; et al. (Mattioli1885, 2024)
Introduction: Atopic dermatitis (AD) is a chronic inflammatory skin disease that negatively impacts the quality of life and work productivity of patients. Objectives: We sought to evaluate the real-world burden of AD patients in Italy. Methods: This sub-analysis of the MEASURE-AD multicountry study conducted between December 2019-2020 included patients diagnosed with moderate-to-severe AD eligible for receiving systemic therapy in the previous 6 months. During a single visit, physician and patient-reported questionnaires were used. Results: A total of 118 adult patients were enrolled and 57.6% (N = 68) of patients had moderate-to-severe AD at the time of enrolment according to the Eczema Area and Severity Index.Sleep disorders interfered with daily function in the previous week in 58.5% (N = 69) of patients, pru-ritus was severe in 50% (N = 59) and 42.4% (N = 50) reported a flare lasting >7 days in the previous 6 months.According to the Dermatology Quality of Life Index, 37.3% (N = 44) of patients reported a severe impact of AD and approximately 10% had clinical depression/anxiety. Current drug therapy was considered inadequate in controlling AD in 26.3% (N=31) of patients.Work activity impairment was 38.6±31.7% and monthly AD-related expenses were 148.6±134.6 Euros per patient. Conclusions: This real-life study documents a high burden of disease in patients with moderate-severe AD in Italy.